Spatio‐temporal motility MRI analysis of the stomach and colon. Issue 5 (28th February 2019) - Menys, Alex; Hoad, Caroline; Spiller, Robin; Scott, S. Mark; Atkinson, David; Marciani, Luca; Taylor, Stuart A.
Abstract: Background: MRI is increasingly used to objectively assess gastrointestinal motility. However, motility metrics often do not offer insights into the nature of contractile action. This study introduces a systematic method of making spatio‐temporal measurements of contractions, based on changes in bowel lumen diameter. Methods: Two heterogeneous cohorts of subjects were selected displaying gastric (n = 15) and colonic motility (n = 20) on which to test the spatio‐temporal motility MRI (STMM) technique. STMM involved delineating the bowel lumen along with inner and outer bowel wall along a section of the gastrointestinal tract. A series of diameter measurements were made automatically across the central axis of the lumen. Measurements were automatically propagated through the time series using a previously validated algorithm. Contractions were quantitatively summarized with two methods measuring (a) normalized contraction plot (NCP) and (b) combined velocity distance (CVD) both of which can be visualized as spatio‐temporal motility maps. Both metrics were correlated against subjective visual scoring systems. Key Results: Good correlation was seen between reader scores and both motility metrics (NCP, R = 0.85, P < 0.001, CVD, R = 0.93, R < 0.001) in the gastric data. Good correlation was also seen between the reader scores and the two metrics in the colonic data (NCP, R = 0.82, P < 0.001, CVD, R = 0.78, R < 0.001). Conclusions and Inferences: Spatio‐temporal motility MRI analysis of the stomach and colon correlates well with reader scores in a range of datasets and provides both a quantitative and qualitative means of assessing contractile activity in the gastrointestinal tract. Abstract : Quantified assessment of gastrointestinal motility using MRI is increasingly common. MRI is a powerful means of observing if the bowel is moving but to date does not tell us about more complex aspects of motility like coordination. Manometry remains the gold standard. This paper applies a spatio‐temporal mapping technique to MRI data enabling systematic measurements of gastric and colonic lumen diameter presenting the data as a spatio‐temporal map that might be evaluated subjectively or quantitatively. Good correspondence between the MRI‐derived spatio‐temporal maps and consensus visual assessment was seen and represents the first step toward improved phenotyping of GI tract motility in health and disease using MRI.